Nesfatin-1, Melatonin, and Cortisol Levels and Eating Behavior Patterns in Shift-Working Healthcare Professionals: A Cross-Sectional Comparative Study - Recai Aci; Ferhat Şi̇ri̇nyildiz; Çağla Öztürk (Galician Medical Journal, 2026)
Introduction. Night-shift work may affect neuroendocrine regulation and eating behavior, but data on the combined assessment of these changes among healthcare professionals remain limited. This cross-sectional study compared six outcomes (serum nesfatin-1, melatonin, and cortisol concentrations and the emotional, external, and restrained eating subscale scores) between daytime and night-shift healthcare professionals. Methods. Eighty healthcare professionals (nurses and other healthcare professionals [physicians/technicians]) were recruited by convenience sampling at a tertiary university hospital and classified into daytime (n = 40) or night-shift (n = 40) groups according to work schedule. Fasting venous blood was collected between 08:00 and 09:00 AM: immediately after the night shift for night-shift workers and after usual nocturnal sleep for daytime workers. Serum nesfatin-1 and melatonin were measured by ELISA; cortisol, insulin, and thyroid hormones were measured by ECLIA. Eating behavior was assessed with the Dutch Eating Behavior Questionnaire (DEBQ). Group comparisons and separate multivariable linear regression models adjusted for age, sex, and body mass index were performed for the six outcomes. Results. The groups were comparable in age, height, body weight, and body mass index (all p > 0.05). Night-shift workers had significantly lower nesfatin-1 and melatonin levels and significantly higher cortisol levels than daytime workers (p < 0.001). DEBQ assessment showed higher emotional and external eating scores among night-shift workers (p < 0.001), while restrained eating scores were lower (p = 0.005). In multivariable regression analysis, night-shift work remained associated with hormonal and eating behavior outcomes after adjustment for age, sex, and body mass index. Conclusions. Night-shift workers had lower morning nesfatin-1 and melatonin concentrations, higher morning cortisol concentrations, higher emotional and external eating scores, and lower restrained eating scores than daytime workers. These cross-sectional, single-time-point findings show group differences but do not establish altered circadian rhythms or causal links between hormone concentrations and eating behavior.